2011
DOI: 10.1007/s00264-011-1241-7
|View full text |Cite
|
Sign up to set email alerts
|

Does multiplex Polymerase Chain Reaction increase the diagnostic percentage in osteoarticular tuberculosis? A prospective evaluation of 80 cases

Abstract: Purpose Multiplex Polymerase Chain Reaction (MPCR) is a technique in which two or more gene targets are amplified in a single reaction. This has increased sensitivity of diagnosis as a single gene target may be absent in some Mycobacterium tuberculosis strains. Methods MPCR using two target genes specific for Mycobacterium tuberculosis, that is, IS6110 and MPB 64, ZN staining and Mycobacterial culture were performed on synovial fluid/pus samples of 80 (three confirmed, 77 suspected) patients of osteoarticular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 17 publications
3
26
0
1
Order By: Relevance
“…We had also reported previously that multiplex targets increase the sensitivity of the tests especially in smear-negative extrapulmonary conditions such as tubercular meningitis and osteoarticular tuberculosis. [7,8] MPCR has many advantages such as less chances of contamination as all reaction takes place in same tube and cost-effective, as stated earlier. [7,8] Therefore, in the present study we evaluated MPCR targeting IS6110 and MPB64 together for diagnosis of the M. tuberculosis complex in clinically suspected TBLA cases.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We had also reported previously that multiplex targets increase the sensitivity of the tests especially in smear-negative extrapulmonary conditions such as tubercular meningitis and osteoarticular tuberculosis. [7,8] MPCR has many advantages such as less chances of contamination as all reaction takes place in same tube and cost-effective, as stated earlier. [7,8] Therefore, in the present study we evaluated MPCR targeting IS6110 and MPB64 together for diagnosis of the M. tuberculosis complex in clinically suspected TBLA cases.…”
Section: Discussionmentioning
confidence: 94%
“…[7,8,12] Multiplex polymerase chain reaction MPCR was performed using primers (Sigma, Bangalore, India) for the IS6110 (IS1: 5'-CCTGCGAGCGTAGGCGT-3' and IS2: 5'-CTCGTCCA GCGCCGCTTCGG-3') and MPB64 (MPB1: 5'-ACC AGGGAGCGGTTCGCCTGG-3' and MPB2: 5'-GATCT GGGGGTCGTCGGAGCT-3') region of the M. tuberculosis complex; amplifi cation conditions have been described earlier. [8] The PCR product was run on 1.5% agarose gel stained with ethidium bromide. Specifi c bands of 123 bp for IS6110 and 240 bp for MPB64 were visualized using a digital gel documentation system (Alpha Innotech, San Leandro, CA, USA) as shown in Figure 1.…”
Section: Deoxyribonucleic Acid Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu yazıda kliniğimize başvuran tüberküloza bağlı spondilodiskit olguları değerlendirilmesi sunulmuştur. (7)(8). Konvensiyonel radyoloji, kas iskelet tüberkülozu olgularının tanısında anahtar role sahiptir.…”
Section: Discussionunclassified
“…However, few studies from different geographical regions of the world have reported that some clinical isolates have either a single copy or no copy of IS6110 which leads to false negative results [24,25]. For avoiding the contamination during amplification and increasing the sensitivity, new approaches such as nested PCR (two step amplification) [26,27] and multiplex PCR (amplification of two or more gene targets simultaneously) [28,29,30,31] have been exploited for EPTB diagnosis.…”
Section: Introductionmentioning
confidence: 99%